EFFECTS OF MATERNAL FOLIC ACID SUPPLEMENTATION AND INTRAUTERINE GROWTH RETARDATION ON EPIGENETIC MODIFICATION OF HEPATIC GENE EXPRESSION AND LIPID METABOLISM IN PIGLETS - J. Liu; B. Yu; X. Mao; Z. Huang; P. Zheng; J. Yu; J. He; D. Chen (Journal of Animal and Plant Sciences, 2014)
The present study was conducted to investigate the effect of maternal folic acid supplementation and intrauterine growth retardation (IUGR) on epigenetic modification of hepatic gene expression and lipid metabolism in weanling piglets. Thirty-two primiparous sows were randomly divided into two dietary groups: control group (C, 1.3 mg/kg folic acid) and folic acid supplemented group (FS, 30 mg/kg folic acid) during gestation. Blood and liver samples of piglets were collected at d 28 postnatal. Intrauterine growth retardation pigs had lower plasma triglyceride, liver triglyceride and total fat than that of normal birth weight (NBW) pigs. Although plasma nonesterified fatty acid (NEFA) was higher for NBW piglets, the birth weight effect was negated in IUGR piglets born to sows fed a FS diet. Hepatic fatty acid synthase (FAS) and Acyl-CoA oxidase (AOX) activities were lower and higher in IUGR piglets, respectively. Methylation status of peroxisomal proliferator-activated receptor-α (PPARα) promoter was lower in IUGR pigs from sows fed a control diet than other groups. Folic acid supplementation reduced the promoter methylation status of glucocorticoid receptor (GR). The mRNA expressions of PPARα, AOX, FAS, phosphoenolpyruvate carboxykinase (PEPCK), and leptin were differentially affected by birth weight. However, mRNA expression of PPARα and FAS in IUGR pigs from sows fed a FS diet was not different from that of NBW pigs. Expression of GR was higher in pigs from mothers fed a FS diet than their counterpart. The present study demonstrated that IUGR changed lipid metabolism and mRNA expression of genes related to this process, and maternal folic acid supplementation was an effective way to prevent the changes by regulating DNA methylation of promoter.
Keywords: DNA methylation; folic acid; intrauterine growth retardation; lipid metabolism; maternal nutrition